The contractor [videorecording (Blu-Ray)] - Pine, Chris, 1980-; Foster, Ben, 1980-; Jacobs, Gillian, 1982-; Marsan, Eddie; Pardo, J. D.; Sutherland, Kiefer, 1966-; Munteanu, Florian; Hoss, Nina; Casar, Amira; Fares, Fares, 1973- (Paramount Home Entertainment, 2022)
Involuntarily discharged from the Army, a Special Forces sergeant lands a contract with a private underground military force. When his very first assignment goes awry, the elite soldier finds himself hunted and on the run, caught in a dangerous conspiracy and fighting to stay alive long enough to get home and uncover the true motives of those who betrayed him.